IMPLEMENTASI NILAI PENDIDIKAN KARAKTER REMAJA MESJID DALAM KEGIATAN BUKA PUASA BERSAMA DI MESJID NURUL HAKIM DI DESA BANGUN KABUPATEN BUTON SELATAN - Kusmawati; Muhammad Ridwan; Rusli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study discusses the implementation of character education values among mosque youth in the iftar (breaking the fast) gathering at Nurul Hakim Mosque in Bangun Village, South Buton Regency. This activity is not only understood as a routine event during the month of Ramadan, but also as a means of character development through social interaction and structured religious activities. The purpose of this study is to determine how character education values are applied in the iftar activities organized by the mosque youth. This research uses a descriptive qualitative approach, with the mosque advisor and youth members as the research subjects. Data were collected through observation, interviews, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. The results show that the iftar gathering serves as a medium for youth character building, with the implemented values including religiosity, discipline, responsibility, cooperation, togetherness, and social concern, which are reflected in the stages of planning, task distribution, implementation, and evaluation of the activity. This activity makes a positive contribution to shaping youth with good morals and social awareness.